2011
DOI: 10.21000/jasmr11010113
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Mined Land Reclamation in the Eastern U. S. Coalfields: A Case for an Ecosystem Reclamation Approach

Abstract: Abstract. The demand for energy throughout the world grows each day, and coal will be needed to meet a large portion of that demand. Coal mining techniques in the Appalachian and Midwestern coalfields have evolved to mine larger land areas and multiple seams at greater depths. New reclamation methods and approaches also must evolve to minimize cumulative impacts on aquatic, terrestrial, and human resources. Mined land reforestation practices over the past 80 years illustrate the evolution of reclamation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Although lasting negative effects from mining can occur in some regions under certain types of mining, such as mountaintop removal in the Appalachian Mountains [9][10][11], research in east Texas has generally found no lasting negative effects for soil and water quality [12][13][14][15][16]. This may be due in part to the fact that the topography is relatively level on the upper Coastal Plain, and the parent materials are less rocky than in other regions.…”
Section: Introductionmentioning
confidence: 99%
“…Although lasting negative effects from mining can occur in some regions under certain types of mining, such as mountaintop removal in the Appalachian Mountains [9][10][11], research in east Texas has generally found no lasting negative effects for soil and water quality [12][13][14][15][16]. This may be due in part to the fact that the topography is relatively level on the upper Coastal Plain, and the parent materials are less rocky than in other regions.…”
Section: Introductionmentioning
confidence: 99%
“…Grassland reclamation is the primary technique used post SMCRA (e.g., Burger 2011;Zipper et al 2011). Grassland reclamation falls under SMCRA, but has led to higher rates of soil compaction and the proliferation of widespread ground covers that slow the natural encroachment of forests (e.g., Angel et al 2009;Groninger et al 2007).…”
Section: Surface Mining Control and Reclamation Act (Smcra)mentioning
confidence: 99%
“…Seeding exotic, invasive plants is an economical way to meet the SMCRA requirements, but these plants offer less value to wildlife compared to native vegetation [4,5]. Furthermore, in Appalachia, typical plantings often are invaded by sericea (Lespedeza cuneata) after approximately a decade [6].…”
Section: Introductionmentioning
confidence: 99%